Electrical properties of various aggregate states of matter - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Electrical properties of solids are caused by elastic polarization of clusters in case of metals while those of dielectrics result from the orientation polarization of induced and built-in electric dipoles. Orientation polarization stems from the interaction of free built-in electric dipoles with an external electric field. A physical model of the dielectric permittivity formation of metals, electrolytes, plasma, ferrites, and ferroelectrics has been developed. Theoretical calculations of the dielectric permittivity of a number of ferrites and barium titanate have been performed in particular.
Keywords: permittivity; aggregate states; metals; plasma; electrolytes; ferroelectrics